Analisis Kinerja Petugas Penanganan Bencana pada Badan Penanggulangan Bencana Daerah Provinsi Daerah Khusus Ibukota Jakarta - Jeffry Listiyadi; Bambang Irawan (Reformasi Administrasi, 2026)
This research is motivated by a phenomenon in The Regional Disaster Management Agency of The Special Capital Region of Jakarta Province that the level of knowledge of officers regarding disasters is still minimal. This research was conducted with the aim of analyzing and evaluating the performance of disaster management officers at The Regional Disaster Management Agency of The Special Capital Region of Jakarta Province in terms of work quality, quantity, timeliness, effectiveness, independence, and work commitment. The research method used is a descriptive qualitative. The results of this study indicate that the performance in terms of work quality, quantity, effectiveness, independence and work commitment has been carried out in accordance with the procedures and performance targets that have been set. However, the aspect of timeliness still needs to be improved. In addition, researcher identified several factors that hinder the performance and the efforts that have been made.